2022
DOI: 10.1002/anie.202214001
|View full text |Cite
|
Sign up to set email alerts
|

Organizing Enzymes on Self‐Assembled Protein Cages for Cascade Reactions

Abstract: Cells use self-assembled biomaterials such as lipid membranes or proteinaceous shells to coordinate thousands of reactions that simultaneously take place within crowded spaces. However, mimicking such spatial organization for synthetic applications in engineered systems remains a challenge, resulting in inferior catalytic efficiency. In this work, we show that protein cages as an ideal scaffold to organize enzymes to enhance cascade reactions both in vitro and in living cells. We demonstrate that not only enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…2,67 Simultaneously, the utility of protein cages is also growing in whole-cell catalysis and metabolic engineering. 35,[68][69][70] Therefore, translational outcomes of protein cage-associated biocatalysis can be expected in industry including pharmaceutical/ fine chemical manufacturing, biofuel/agricultural production, and environmental remediation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,67 Simultaneously, the utility of protein cages is also growing in whole-cell catalysis and metabolic engineering. 35,[68][69][70] Therefore, translational outcomes of protein cage-associated biocatalysis can be expected in industry including pharmaceutical/ fine chemical manufacturing, biofuel/agricultural production, and environmental remediation.…”
Section: Discussionmentioning
confidence: 99%
“…73 A recent study showed the efficiency of a cascade reaction was enhanced by inter-enzyme proximity, which was induced by co-localization of the cascade enzymes on the exterior surface of a protein cage. 68 The molecular mechanism behind the increased efficiency, however, needs to be further investigated in the future. using biomimetic approaches.…”
Section: Naturally Occurring Metabolons Formed By Protein Cages Induc...mentioning
confidence: 99%
See 1 more Smart Citation
“… [73] Likewise, Kang et al. showed a globular protein cage Mi3 from E. coli as a scaffold to organize three enzymes for lycopene biosynthesis, leading to an 8.5‐fold increase in cellular production [74] . Lim et al.…”
Section: Scaffolded Enzyme Assemblymentioning
confidence: 99%
“…[73] Likewise, Kang et al showed a globular protein cage Mi3 from E. coli as a scaffold to organize three enzymes for lycopene biosynthesis, leading to an 8.5-fold increase in cellular production. [74] Lim et al also utilized a self-assembling filamentous protein, the γprefoldin (γ-PFD), to form the scaffold. The scaffold was engineered to display an array of peptide tags, through which enzymes can be assembled (Figure 2E).…”
Section: Assembly On Protein Scaffoldsmentioning
confidence: 99%